Cost-effective track and trace technology for poor-quality chemotherapeutic pharmaceuticals in resource-limited countries: a review of the Chemotherapeutic Paper Analytical Device - Worku, Minichil Chanie; Limenh, Liknew Workie; Mekonnen, Biset Asrade; Anagaw, Yeniewa Kerie (Frontiers in Medical Technology, 2024)
Medicines that are poor-quality (substandard or counterfeited) can lead to treatment failure. There was a vast global imbalance in cancer treatment outcomes due to difficulty of accessing quality chemotherapeutic products. Earlier diagnosis brings more hope for curative treatment of cancer and increases the demand for chemotherapeutic products. Consequently, it creates opportunities for unethical manufacturers and suppliers to come up with substandard and/or counterfeited products. An ongoing review of cost-effective analytical methods is therefore paramount to tracking and tracing poor chemotherapeutic pharmaceutical products. Low- and Middle-Income Countries (LMICs) regulators lack safety equipment and standard operating procedures to handle chemotherapeutic products safely in the drug analysis laboratory and have limited capacity to perform post-marketing surveillance on these products. The aim of the review was to provide a compressive review about Chemotherapeutic Paper Analytical Device (ChemoPAD). ChemoPAD is an important method for quality screening of commonly used chemotherapeutic products in LMIC’s settings. It is an efficient, fast, simple, accessible, cost-effective, and transferable analytical method that can be used for verification of substandard and/or counterfeited chemotherapeutic products. It was designed as a complete laboratory on a piece of paper with a playing card size. ChemoPAD is a promising technology for healthcare providers, patients, and other parties involved in post-marketing surveillance services for chemotherapeutic products. Thus, in the near future, scientists could probably witness the use of ChemoPAD technology platform to trace and track substandard and/or counterfeited chemotherapeutic products.